Earthquake-Related Changes in Species Spatial Niche Overlaps in Spring Communities - Simone Fattorini (Scientific Reports, 2017)
Abstract Species interactions between stygobites (obligate groundwater organisms) are poorly known, reflecting the difficulty in studying such organisms in their natural environments. Some insight can be gained from the study of the spatial variability in microcrustacean communities in groundwater-fed springs. Earthquakes can increase hydraulic conductivity in the recharge area of karstic aquifers and flow rates in discharge zones, thus dislodging stygobites from their original habitats to the spring outlets. Earthquakes are expected to alter species spatial niche overlap at the spring outlets, where stygobites coexist with non-stygobites living in benthic and subsurface habitats. We compared the abundance of stygobiotic and non-stygobiotic microcrustaceans in groundwater-fed springs before and after the 6.3-Mw earthquake that hit the karstic Gran Sasso Aquifer (Italy) in 2009. Pre-seismic (1997, 2005) overall niche overlaps were not different from null expectations, while post-seismic (2012) species mean niche overlaps were higher, following the redistribution of animals caused by the earthquake-triggered discharge. The reduced abundance of stygobites following their dislodgement from the aquifer and the concomitant displacement of non-stygobites led to a higher post-seismic co-occurrence of stygobites and non-stygobites. Changes in aquifer structure destroyed pre-seismic species segregation patterns by creating new or strengthening already existing interactions.